2020
DOI: 10.1111/ejh.13493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and risk factors for mortality from COVID‐19 in patients with haematological malignancies

Abstract: Background: The impact of coronavirus disease 2019 (COVID-19) in haematological patients (HP) has not been comprehensively reported. Methods: We analysed 39 patients with SARS-CoV-2 infection and haematological malignancies. Clinical characteristics and outcomes were compared to a matched control group of 53 non-cancer patients with COVID-19. Univariate and multivariate analyses were carried out to assess the risk factors associated with poor outcome. Results: The most frequent haematological diseases were lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 43 publications
7
109
2
4
Order By: Relevance
“…A total of 5121 patients with cancer in 29 studies were included in this meta-analysis. [6][7][8][9][10][11] The characteristics of the studies included in this meta-analysis are presented in Table 2. Of the remaining 29 studies, eight were conducted in China, six in the United States, four in the United Kingdom, three in Spain, two in France, two in Italy, and four was performed in multiple countries.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 5121 patients with cancer in 29 studies were included in this meta-analysis. [6][7][8][9][10][11] The characteristics of the studies included in this meta-analysis are presented in Table 2. Of the remaining 29 studies, eight were conducted in China, six in the United States, four in the United Kingdom, three in Spain, two in France, two in Italy, and four was performed in multiple countries.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, emerging studies suggest that COVID-19-infected cancer patients receiving systematic anticancer therapy are at a higher risk than those who receive no antitumor treatment, 8 especially hematological patients receiving chemotherapy. 9 Interestingly, there are also clinical studies strongly, indicating that anticancer treatments have no deteriorating effects on clinical outcomes. 10,11 Thus, whether COVID-19-infected cancer patients with versus without anticancer treatments have a higher risk of unfavorable clinical outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Following a nosocomial outbreak of COVID-19 in a hematological oncology unit in Central Europe, 36.8% of their patients died [7] ; nearly a third (30.6%) of the 1044 patients in the UK Cancer Coronavirus Monitoring Project died, the vast majority of whom (92.5%) had cause of death recorded as COVID-19 [18] . Another study by Sanchez-Pina et al., reported that patients with hematologic malignancies had COVID-related mortality of 35.9% versus 13.2% in COVID-positive, non-cancer, age- and illness-severity-matched controls ( p = 0.003, OR 6.652) [9] ; and in a retrospective chart review of 1878 COVID-19 patients, 52.3% (9/17) of the lung cancer patients died compared to just 10.2% COVID-19 mortality in the general population at the same center ( p <0.0001), though it should be noted that a majority of the lung cancer patients had metastatic malignancy (11/17) and comorbidities such as hypertension (10/17) and chronic obstructive pulmonary disorder (COPD) (9/17) [20] . Regardless, these numbers illustrate how severe COVID-19 infection can be for cancer patients.…”
Section: Introductionmentioning
confidence: 97%
“…Due to health anxieties and desire to avoid viral exposure, some cancer patients have delayed or paused treatments [8] . Certain key biomarkers, including C-reactive protein (CRP), interleukin-6 (IL-6), and others are being investigated for prognostic capability and treatment course determination in cancer patients with COVID-19 [9] , [10] , [11] . Guidelines are currently being developed to determine treatment priorities on the basis of risk stratifications [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation